The Effect Of Debt To Equity Ratio, Debt To Asset Ratio, And Sales Growth On Financial Performance In Transportation And Logistics Sector Companies In The Period 2019-2024 - Ima, Ima Andriyani; Marzuki, Agustina; Suharti, Suharti; Efrizal, Herman; Sahila, Sahila (Universitas Dehasen Bengkulu, 2025)
This study aims to examine the effect of debt to equity ratio, debt to asset ratio and sales growth on financial performance in transportation and logistics sector companies listed on the Indonesia Stock Exchange in 2019-2024. This study uses a quantitative method. The population in this study were 35 transportation and logistics sector companies. The sample in this study was eight companies. The data collection technique in this study used documentation techniques. The data analysis technique in this study used descriptive statistical analysis, classical assumption tests, and multiple linear regression tests, and hypothesis tests. The data sources used are secondary data obtained from the official IDX website (www.idx.co.id) and the official website of the company concerned. The population in this study were transportation and logistics sector companies listed on the Indonesia Stock Exchange in 2019-2024. The sampling technique was carried out using purposive sampling. This study produces; (1) There is a positive influence between Debt to Equity Ratio on financial performance. (2) There is an influence between debt to asset ratio on financial performance (3) There is an influence between sales growth on financial performance. (4) There is an influence between debt to equity ratio (DER), and debt to asset ratio (DAR), sales growth on financial performance in transportation and logistics sector companies listed on the Indonesia Stock Exchange in 2019-2024. (5) R Square of the three independent variables, namely debt to equity ratio, debt to asset ratio and sales growth, is able to influence the dependent variable, namely financial performance by 79.5% and the other 20.5% is influenced by other factors outside this study. The implications of this study emphasize the importance of managing a healthy capital structure, both through Debt to Equity Ratio (DER) and Debt to Asset Ratio (DAR), to improve the company's financial performance. In addition, positive sales growth has also been proven to be significant in supporting financial performance. Therefore, companies in the transportation and logistics sector can utilize these findings by more strategically managing debt, assets, and increasing sales to maintain competitiveness and attract investor interest. These findings are also relevant for policy makers to formulate regulations that support the growth of the sector.